2016
DOI: 10.5056/jnm16013
|View full text |Cite
|
Sign up to set email alerts
|

Laryngopharyngeal Reflux in Children with Chronic Otitis Media with Effusion

Abstract: Background/AimsTo evaluate the characteristic properties of laryngopharyngeal reflux (LPR) and gastroesophageal reflux (GER) in children with otitis media with effusion (OME) using 24-hour multichannel intraluminal impedance combined with dual-probe (pharyngeal and esophageal) pH-metry. MethodsChildren aged 7-10 years of age with OME underwent 24-hour multichannel intraluminal impedance pH-metry. The upper pH sensor was situated 1 cm above the upper esophageal sphincter, and the lower pH sensor was placed 3-5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 23 publications
(21 reference statements)
2
27
0
Order By: Relevance
“… , extraoesophageal reflux is probably one of the aetiological factors in as many as one‐third of the children with OME. That statement is absolutely in line with the results of our study and the results of a previously cited study from Poland . All these studies used MII‐pH monitoring to evaluate children with OME, emphasising further its usefulness in the diagnosis of GER‐related OME.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“… , extraoesophageal reflux is probably one of the aetiological factors in as many as one‐third of the children with OME. That statement is absolutely in line with the results of our study and the results of a previously cited study from Poland . All these studies used MII‐pH monitoring to evaluate children with OME, emphasising further its usefulness in the diagnosis of GER‐related OME.…”
Section: Discussionsupporting
confidence: 92%
“…In 2016, Górecka‐Tuteja et al. investigated 28 children aged 7–10 years of age with OME using MII‐pH monitoring and found pathological GER in 35.7% of the children. These data in that study were in accordance with our findings, as we found that 35% of children had GERD but, interestingly, we found a higher proportion of weakly acidic GER episodes.…”
Section: Discussionmentioning
confidence: 99%
“…LPR is considered one of the risk factors of OM. In the study by Górecka-Tuteja et al, 10 19 of 28 children (68%) with OM had LPR, which is similar to the results found in previous studies (mean 49%, range 27-71%). 8 Therefore, the authors suggest that LPR is an important risk factor of OM in children.…”
supporting
confidence: 80%
“…the eustachian tube may be attributed to mucosal inflammation, toxicity, and osmosis of bile acid in an acidic environment after LPRD [17]. LPRD is associated with the occurrence and progress of secretory otitis media [18], and it can make secretory otitis media progress more rapidly [19]. Obesity is one of the influencing factors of LPRD, and patients with an abnormal BMI often have a high risk of LPRD [20].…”
Section: Discussionmentioning
confidence: 99%